Proteome adaptations of the organohalide-respiring Desulfitobacterium hafniense strain DCB-2 to various energy metabolisms - Willemin, Mathilde Stéphanie; Hamelin, Romain; Armand, Florence; Holliger, Christof; Maillard, Julien (Frontiers in Microbiology, 2023)
Desulfitobacterium hafniense was isolated for its ability to use organohalogens as terminal electron acceptors via organohalide respiration (OHR). In contrast to obligate OHR bacteria, Desulfitobacterium spp. show a highly versatile energy metabolism with the capacity to use different electron donors and acceptors and to also grow fermentatively. Desulfitobacterium genomes display numerous and apparently redundant members of redox enzyme families which confirm their metabolic potential. Nonetheless, the enzymes responsible for many metabolic traits are not yet identified. In the present work, we conducted an extended proteomic study by comparing the proteomes of D. hafniense strain DCB-2 cultivated in combinations of electron donors and acceptors, triggering five alternative respiratory metabolisms that include OHR, as well as fermentation. Tandem Mass Tag labelling proteomics allowed us to identify and quantify almost 60% of the predicted proteome of strain DCB-2 (2796 proteins) in all six growth conditions. Raw data are available via ProteomeXchange with identifier PXD030393. This dataset was analysed in order to highlight the proteins that were significantly up-regulated in one or a subset of growth conditions and to identify possible key players in the different energy metabolisms. The addition of sodium sulfide as reducing agent in the medium – a very widespread practice in the cultivation of strictly anaerobic bacteria – triggered the expression of the dissimilatory sulfite reduction pathway in relatively less favourable conditions such as fermentative growth on pyruvate, respiration with H2 as electron donor and OHR conditions. The presence of H2, CO2 and acetate in the medium induced several metabolic pathways involved in carbon metabolism including the Wood-Ljungdahl pathway and two pathways related to the fermentation of butyrate that rely on electron-bifurcating enzymes. While the predicted fumarate reductase appears to be constitutively expressed, a new lactate dehydrogenase and lactate transporters were identified. Finally, the OHR metabolism with 3-chloro-4-hydroxyphenylacetate as electron acceptor strongly induced proteins encoded in several reductive dehalogenase gene clusters, as well as four new proteins related to corrinoid metabolism. We believe that this extended proteomic database represents a new landmark in understanding the metabolic versatility of Desulfitobacterium spp. and provides a solid basis for addressing future research questions.